IDEF0 measurement planning model for a workpiece machined by a CNC lathe. (1st January 2002) - Lin, Zone-Ching; Lin, Cong-Zhi
In the past, most research concerning coordinate measuring machines (CMM) concentrated on the automation of measuring process planning. However, a comprehensive analysis of the entire measuring operation should be conducted using a systematic method, before the application of any of the planning techniques. This systematic analysis should consider measuring planning and inspection operations at the same time to let measuring operations be incorporated into the entire manufacturing system. In this article, the workpiece machined by a CNC lathe is used to study the planning of the measuring process, and an IDEF0 planning model for measuring sequence and activities of the CMM is proposed. The measurement planner and the production system designer may then clearly understand the relationship among the different functions of the measuring system to enable the system integration problem to be solved more easily.